Luteolin Improves Insulin Resistance in Postmenopausal Obese Mice by Altering Macrophage Polarization (FS12-01-19). (13th June 2019) - Baek, Yunjung; Lee, Mi Nam; Wu, Dayong; Pae, Munkyong
Abstract: Objectives: Previously, we showed that loss of ovarian function in mice fed high-fat diet exacerbated insulin resistance and adipose tissue inflammation. In the current study, we tested whether consumption of luteolin, an anti-inflammatory flavonoid, could mitigate adipose tissue inflammation and insulin resistance in obese ovariectomized mice. Methods: Nine-week-old ovariectomized C57BL/6 mice were fed a low-fat diet (LFD), high-fat diet (HFD), or HFD supplemented with 0.005% luteolin (HFD + L) for 16 weeks. The anti-inflammatory drug salicylate was used as a positive control. Fasting blood glucose, insulin, and insulin resistance index HOMA-IR were measured every 4 weeks. Adipose tissue and spleen were characterized for tissue inflammation by real-time PCR and immune cell populations by flow cytometry after 16 weeks of feeding. Results: HFD resulted in more body weight gain than LFD in ovariectomized mice and supplementing HFD with 0.005% luteolin did not affect the body weight gain. In addition, HFD elicited a significant elevation in fat mass, which were comparable between HFD and HFD + L groups. However, luteolin supplementation resulted in a significant decrease in CD11c + macrophages in gonadal adipose tissue, as well as a trend of decrease in macrophage infiltration. Luteolin supplementation also significantly decreased mRNA expression of inflammatory and M1 markers MCP-1, CD11c, TNF-a, and IL-6, while maintaining expression of M2 marker MGL1. We further found that luteolin treatment protected mice from insulin resistance induced by HFD consumption; this improved insulin resistance was correlated with reductions in CD11c + adipose tissue macrophages. Conclusions: Our findings indicate that dietary luteolin supplementation attenuates adipose tissue inflammation and insulin resistance found in mice with loss of ovarian function coupled with a HFD intake, and this effect may be partly mediated through suppressing M1-like polarization of macrophages in adipose tissue. These results have clinical implication in implementing dietary intervention for prevention of metabolic syndrome associated with postmenopause and obesity. Funding Sources: Supported by the National Research Foundation of Korea (NRF) grant funded by the Korea government (MSIP) (NRF-2018R1A1A1A05078886).